Ouratea spectabilis and its Biflavanone Ouratein D Exert Potent Anti-inflammatory Activity in MSU Crystal-induced Gout in Mice - Rocha, Marina P.; Oliveira, Diego P.; de Oliveira, Vivian L. S.; Zaidan, Isabella; Grossi, Laís C.; Campana, Priscilla R. V.; Amaral, Flávio A.; Sousa, Lirlândia P.; Teixeira, Mauro M.; Braga, Fernão C. (Planta Medica, 2023)
Gouty arthritis (GA) is an inflammatory arthritis triggered by the deposition of monosodium urate monohydrate (MSU) crystals, causing pain, inflammation, and joint damage. Several drugs are currently employed to manage acute flares of GA, but they either have limited effectiveness or induce severe adverse reactions. Ouratea spectabilis is traditionally used in Brazil to treat gastric ulcers and rheumatism. The ethanolic extract of O. spectabilis stems (OSpC) and four biflavanones (ouratein A – D) isolated thereof were evaluated in a murine model of GA induced by the injection of MSU crystals. The underlying mechanism of action of ouratein D was investigated in vitro in cell cultures by measurement of IL-1β levels by ELISA and Western blot analysis. The administration of OSpC (10, 30 or 100 mg/Kg, p. o.) reduced the migration of total inflammatory cells, monocytes, and neutrophils and diminished the levels of IL-1β and CXCL1 in the synovial tissue. Among the tested compounds, only ouratein D (1 mg/Kg) reduced the migration of the inflammatory cells and it was shown to be active up to 0.01 mg/Kg (equivalent to 0.34 nM/Kg, p. o.). Treatment of pre-stimulated THP-1 cells (differentiated into macrophages) or BMDMs with ouratein D reduced the release of IL-1β in both macrophage lines. This biflavanone reduced the activation of caspase-1 (showed by the increase in the cleaved form) in supernatants of cultured BMDMs, evidencing its action in modulating the inflammasome pathway. The obtained results demonstrate the anti-gout properties of O. spectabilis and point out ouratein D as the bioactive component of the assayed extract.
Keywords: Ouratea spectabilis; Ochnaceae; gouty arthritis; biflavanones; ouratein D; caspase-1 inhibitors